Analysis of the Impact of Covid-19 Pandemic on the Economy of Surakarta - Rizqi, Risa Ayu Riana; Sunariya, M. Iqbal Taufiqurrahman (Universitas Muhammadiyah Surakarta, 2021)
SARS-Cov 2 is a virus that spreads throughout the world that can cause death and have a major impact on the national economy, especially the City of Surakarta experiencing high economic losses which can lead to increased unemployment. The Covid-19 pandemic has had a major impact on the process of economic flow in society. Many people complain and the cessation of their mobility and activities due to the Covid-19 virus pandemic. One of the sectors of community life that has been affected by the COVID-19 pandemic is the tourism sector. This study aims to describe the impact of Covid-19 on the economy in Surakarta City. This research method uses descriptive quantitative methods and the following research was carried out in the Surakarta City area. The impact of COVID-19 uses secondary data, including agency surveys and literacy studies as well as conducting descriptive statistical analysis and data tabulation. The results of this study are the impact of COVID-19 on seven research objects, including tourism, unemployment, inflation, layoffs (PHK), exports and imports, regional taxes, and investment. The decline in several sectors affected regional income, so that economic growth in Surakarta weakened. One sector that shows the affected status is tourist attraction which in 2019 was worth 3,562,551 people and in 2020 it decreased to 354,107 people, meaning that tourist attractions in Surakarta lost 3,208,444 people, this is one of which is influenced by the presence of regulations from the government regarding large-scale social restrictions (PSBB) which result in offices and most industrial activities being prohibited from producing, for an undetermined period of time, and causing economic losses.